CORRELATION BETWEEN SERUM LEVELS OF FOLLICLE STIMULATING HORMONE AND GRAAFIAN FOLLICLE VASCULARITY ON DOPPLER IN INFERTILE FEMALES OF LAHORE: Follicle Stimulating Hormone and Graafian Follicle Vascularity - Iqbal, Amjad; Gilani, Syed Amir; Hanif, Asif (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine correlation between serum levels of Follicle Stimulating Hormone and Graafian Follicle vascularity on Doppler ultrasound in infertile females of Lahore, Pakistan.Study Design: Cross sectional study.Place and Duration of Study: Prime Ultrasound center, 2-Shalamrar Link Road, Mughalpura, Lahore, Pakistan From Mar 2018 to Sep 2019.Methodology: A total of 100 infertile females using simple random sampling were taken. All the married women of reproductive age and married for >12 months who have not conceived despite regular unprotected intercourse, having no other uterine and endometrial or ovarian pathology were taken. The patients who fail to provide serum hormone laboratory reports were excluded. Transvaginal ultrasonography was done for all females and graafian follicle vascularity on Doppler was measured on day 12 of the cycle.Results: The Median age of females was 28 (30-25) years range from 19 and 46 years. The median Follicle Stimulating Hormone levels at day 12 was 6 (8.25-5.22) mlU/ml with minimum and maximum FSH values as 3.20 and 40 mlU/ml. The median follicle size was 13.65 (16.04-10.84) (mm) with minimum and maximum size as 10 mm and 26 mm. There were 61% females who had Grade–1 perifollicular vascularity, 24% females had grade-2 and 15% females had grade-3 of perifollicular vascularity. There was significant positive correlation between perifollicular vascularity grades and Follicle-stimulating hormone levels day 12 (mm) i.e., r=0.309, p-value